The notion of the constitutional right to higher education, its content and structure - Drobysh, Olga V. (Journal of the Belarusian State University. Law, 2019)
The article gives a thorough and profound analysis of the notion of the constitutional right to higher education, its structure and content. Author’s interpretation of the concept of «right to higher education» is based on the approaches suggested by native and foreign scholars, however, research is being conducted in the context of the Belarusian legislation. Based on the analysis of international legal instruments and national legislation in the aspect of different classifications, the specific features of the given right that determines its special place in the system of rights and freedoms of the individual have been defined. Due to universal character of the right to higher education these features are characterized by different types of rights and freedoms. The author states that, with features of universal rights, the right to higher education is a right, limited by public and state interests. It is concluded that the content of the concept of the right to higher education includes: the right to access to higher education on a competitive basis, right to higher education without any discrimination, the right to quality education, the right to academic freedom, the right to education in the framework of academic mobility, the right to choose the language of instruction.
Keywords: right to higher education; the essential properties of the right to higher education; academic freedom